Synthesis of Anti-oxidant Steroids by Hybridisation with Nitroxides - Soltau, Carl P.; Weir, Naomi E.; Martyn, Alexander P.; Bottle, Steven E. (Synthesis, 2024)
Steroidal–nitroxide hybrid molecules and non-radical controls were synthesised in good yields using simple carbodiimide coupling. An unexpected product arose from reactions between the nitroxide moiety and the solvent THF. Methoxyamine derivatives of the nitroxide drug hybrids were produced using Fenton chemistry without side reactions occurring on the steroid. The hybrid compounds bind to the glucocorticoid receptor and are relevant for the study of radical biological chemistry and redox-related disease processes.
Keywords: nitroxides; anti-oxidants; steroids; glucocorticoid; radicals